2004
DOI: 10.1161/01.cir.0000140675.85342.1b
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of the Combination of Clopidogrel and Aspirin in Patients Undergoing Surgical Revascularization for Non–ST-Elevation Acute Coronary Syndrome

Abstract: Background-Antiplatelet therapy and antithrombin therapy have been demonstrated to reduce the risk of cardiac events in patients presenting with acute coronary syndrome, yet all effective therapies also increase the risk of bleeding. Methods and Results-In the Clopidogrel in Unstable angina to prevent Recurrent ischemic Events (CURE) trial, 12 562 patients were randomized to clopidogrel or placebo in addition to aspirin, and the primary outcome was cardiovascular (CV) death, myocardial infarction (MI), or stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
173
0
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(207 citation statements)
references
References 24 publications
3
173
0
13
Order By: Relevance
“…In 2003, percutaneous coronary intervention was applied as the gold standard for acute ST-elevation MI in Denmark [10] and the use of beta-blockers, statins and platelet inhibitors has markedly increased [11][12][13][14]. However, no decline of relative risk was demonstrated when comparing the incident MI patients from the two time periods.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, percutaneous coronary intervention was applied as the gold standard for acute ST-elevation MI in Denmark [10] and the use of beta-blockers, statins and platelet inhibitors has markedly increased [11][12][13][14]. However, no decline of relative risk was demonstrated when comparing the incident MI patients from the two time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the delay to surgery seems longer for ticagrelor despite its having a shorter half‐life compared with clopidogrel. Importantly, the observed duration from catheterization to CABG is significantly shorter than that seen in the clinical trials studying this topic previously 12, 13. The reluctance of clinicians to wait the recommended period may be possibly explained by a bias toward earlier revascularization5, 14; only a small proportion of NSTEMI patients treated with precatheterization P2Y 12 inhibitors deferred CABG to another hospitalization after the index NSTEMI hospitalization.…”
Section: Discussionmentioning
confidence: 95%
“…In a subgroup analysis of CABG patients in the CURE trial,12 pretreatment with clopidogrel was found to have similar clinical benefits without incurring increased risk of bleeding when CABG was performed more than 5 days after drug cessation but was associated with increased life‐threatening bleeding when clopidogrel was discontinued less than 5 days before CABG. Our study again showed that bleeding and transfusion rates were higher when CABG occurred within 5 days of precatheterization P2Y 12 inhibitor exposure, compared with CABG that occurred >5 days afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…52 The benefits and risks of clopidogrel were analyzed recently in patients undergoing CABG for non-ST elevation acute coronary syndrome. 67 The benefits of clopidogrel (re-introduced after six to 25 days after surgery) overweighed the bleeding risk. However, data indicate that the use of clopidogrel within three to five days before surgery is associated with increased bleeding.…”
Section: Antiplatelet Therapy In the Prevention Of Graft Occlusion Anmentioning
confidence: 99%
“…However, data indicate that the use of clopidogrel within three to five days before surgery is associated with increased bleeding. 67,68 Therefore, cessation of clopidogrel at least five days before surgery, when possible, is clearly recommended. When clopidogrel has not been stopped before surgery (for example, emergency procedure), the use of antifibrinolytics (aprotinin, epsilon-aminocaproic acid or tranexamic acid) could be proposed, since such treatments decrease postoperative blood loss and transfusion requirements, without increasing early graft closure.…”
Section: Antiplatelet Therapy In the Prevention Of Graft Occlusion Anmentioning
confidence: 99%